Criopreservação do sêmen asinino coletado de forma fracionada e envasado em FlatPacks ou palhetas de 0,55 mL: características espermáticas e taxa de gestação de éguas com ovulação induzida - Amanda Luiza Ribeiro Sales (2011)
The present study was conducted from September of 2010 to February of 2011, in Lagoa Dourada, Minas Gerais, the southest region of Brazil. The objectives of this study were evaluate a) in vitro characteristics of the sperm-rich fraction of jackass semen, using fractional collection of semen carried out by the split-ejaculate method throughout of cooling, freezing and thawing process (Experiments I and II EI and EII), b) pregnancy rates of the mares inseminated with frozen jackass semen packed in FlatPacks (EIII), c) time interval between the use of hCG and ovulation in mares. In EI and EII the sperm-rich fraction of five Pêga jackasses was frozen using modified Nagase e Niwa (1964) extender, with 20% of egg yolk and 3.5% of glycerol. After dilution two cooling rates were used: a fast one in EI and a slow one in EII and semen was packed in FlatPacks (05 mL) or in straws (0.55 mL). A modified protocol by Martin et al. (1979) was used for freezing. In EIII 16 mares received hCG (1.666 UI) to induce ovulation when they had a follicle with 3.4 cm of diameter and uterine edema.The inseminations were carried out in the uterine body (T1) or in the tip of the uterine horn (T2). Overall 71.19% of the post-thaw semen was approved on in vitro experiments (motility 30%; vigor 3), but the pregnancy rates/cycle were 0%. The jackasses used were different about seminal characteristics, with huge individual variation. The approved post-thaw semen was affected by jackasses, cooling rates and kind of package, with best results for semen processed in a slow cooling rate and packed in straws. hCG (1.666 UI) was efficient to induce ovulation in a time interval of 30-42 hours pos-induction. The seminal plasma removal, using split-ejaculate method, associated with 20% of egg yolk and 3.5% of glycerol extender had a contraceptive effect. The results showed that in vitro results do not always reflect the in vivo results.